1999
DOI: 10.1037/0022-0663.91.3.403
|View full text |Cite
|
Sign up to set email alerts
|

Phonological awareness and early reading: A meta-analysis of experimental training studies.

Abstract: In a quantitative meta-analysis, the effects of phonological awareness training on reading were shown. In a homogeneous set of U.S. studies with a randomized or matched design, the combined effect sizes for phonological awareness and reading were d = 0.73 (r = .34, N = 739) and d = 0.70 (r = .33, N = 745), respectively. Thus, experimentally manipulated phonological awareness explains about 12% of the variance in word-identification skills. The combined effect size for long-term studies of the influence of phon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
398
7
52

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 655 publications
(492 citation statements)
references
References 54 publications
(64 reference statements)
35
398
7
52
Order By: Relevance
“…As expected from the Wood et al (2009) model and a wealth of past studies the variables suggested to mediate between prosody and literacy, namely phonological awareness comprising both phoneme and rhyme (Anthony & Lonigan, 2004;Bus & van Ijzendoorn, 1999;Cain, 2010;Snowling, 2000) and morphological awareness (e.g., Deacon et al, 2009;Kirby et al, 2008;Nunes & Bryant, 2009) were able to make independent contributions to reading and spelling when all other variables were controlled for. Vocabulary made a contribution when entered to the model alone but not when the other variables were entered supporting the assertion that its primary effect is on phonological awareness (Walley, 1993) which then in turn influences literacy as mentioned above.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…As expected from the Wood et al (2009) model and a wealth of past studies the variables suggested to mediate between prosody and literacy, namely phonological awareness comprising both phoneme and rhyme (Anthony & Lonigan, 2004;Bus & van Ijzendoorn, 1999;Cain, 2010;Snowling, 2000) and morphological awareness (e.g., Deacon et al, 2009;Kirby et al, 2008;Nunes & Bryant, 2009) were able to make independent contributions to reading and spelling when all other variables were controlled for. Vocabulary made a contribution when entered to the model alone but not when the other variables were entered supporting the assertion that its primary effect is on phonological awareness (Walley, 1993) which then in turn influences literacy as mentioned above.…”
Section: Discussionmentioning
confidence: 59%
“…Regarding vocabulary, it was argued that sensitivity to syllabic stress (which is louder, articulated more forcefully, higher in pitch, and longer in duration) might facilitate spoken word segmentation and recognition given that 85% of lexical words in English begin with a strong syllable (Cutler & Carter, 1987). Growth in vocabulary supports the development of phonological awareness (Walley, 1993), a skill that has been extensively linked to early reading and spelling attainment (e.g., Bus & van Ijzendoorn, 1999;Cain, 2010;Snowling, 2000) and thus would ultimately support written word recognition.…”
Section: Prosody and Early Literacymentioning
confidence: 99%
“…This argument also extends to the impact that phonological programs have on the prevention of learning difficulties. Bus, Marinus, and Ijzendoorn (1999) analysed the impact that 36 experimental phonological training studies had on learning to read and concluded that this type of intervention program significantly affects both the promotion of phonological awareness and e albeit to a lesser extent e reading skills. At the same time, when he looked at the methodological characteristics of this type of study, Troia (1999) confirmed the positive effect that phonological training has on phonemic synthesis and analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Estudios de entrenamiento en conciencia fonológica con pequeños grupos de niños han mostrado que es posible mejorar los niveles de sensibilidad fonológica de los niños a través de la intervención sistemática (Borzone, 1997;Bradley & Bryant, 1883;Bus & van Ijzendoorn, 1999;Defi or & Tudela, 1994;Ehri et al, 2001;Hecht & Close, 2002;Signorini & Borzone, 1996). Asimismo, existe evidencia creciente de que las intervenciones con grupos de clase completos pueden dar lugar a incrementos considerables (Borzone, 1997;Ehri et al, 2001).…”
Section: Discussionunclassified